The Pulse of Digital Payments: Understanding UPI App Preferences (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
UPI has become a widely accepted and preferred payment mode since its inception in 2016 in India. UPI is an advanced payment system which offers greater ease of use for consumers along with high security and it has shown greater adoption by the people. In 2008 demonetization and then covid-19 led to the growth in online and digital mode of payment. Availability of highspeed uninterrupted internet further facilitates the acceptance of UPI mode in urban as well as rural area. According to the studies India's digital payments volume has increased at an average annual rate of about 50 percent over the last five years. This study intends to understand the factors influencing customer preferences towards UPI apps. This study was conducted in Kalol and Gandhinagar districts of Gujarat. Simple Random sampling method was used to select 203 respondents for the study. The influence of various factors like convenience, popularity, safety, ease of access was analysed to know customer preferences for UPIs. Test like ANOVA and t-Test were used for analysis. The results indicate that customers have a favourable opinion for unified payment interface method. The usage of UPI services is positively correlated with the respondents' level of education. Customers prefer UPI app that offer more safety and trustworthiness over convenience, popularity and other services like cash back and rewards.